(untitled) (Al-Academy, 2023)
This research aims to study and reveal the influence of Bauhaus principles in contemporary graphic design. The researcher determined the objective/spatial/temporal limit: Study of the Bauhaus influence in the design of the graphic poster in Germany in 2020. The theoretical framework in the first section dealt with (the emergence and factors of the emergence of the Bauhaus school and its characteristics), while the second topic dealt with (the intellectual, functional and aesthetic data of the Bauhaus School), after which the indicators that resulted from the theoretical framework were produced. He mentioned four previous studies, one of them was discussed in detail. In the third chapter he defined the methodology, society, and sample of the research and analyzed the selected models. In the fourth chapter, the following results were produced: The sample appeared expressing the most important functional data of the Bauhaus and its implications for the graphic design. The designers used the most important formal data of the Bauhaus by employing geometric shapes. The conclusions were: that the formal influence of the Bauhaus in the design of the poster came as a result of employing these data in all the sample models. The research concluded with recommendations and suggestions, a list of sources and an abstract in English.